Generations and politics : a panel study of young adults and their parents - Jennings, M. Kent; Niemi, Richard G. (Princeton legacy library, 1981)
Kent Jennings and Richard Nieini arc recognized widely for their 1965 study of the development of political attitudes and behavior among a large, nationally representative sample of high school seniors and their parents (The Political Character of Adolescence, Princeton). Now they present the results of a follow-up study of these same individuals in 1973 along with a fresh study of 1973 high school seniors. Spanning a dramatic eight-year historical period and an important transitional phase in the life cycle of the younger generation, this material provides a unique opportunity to assess the development of political attitudes and participation. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.